The Chemistry and Biological Effects of Thioflavones - Dong, Jinyun; Zhang, Qijing; Meng, Qingqing; Wang, Zengtao; Li, Shaoshun; Cui, Jiahua (Mini Reviews in Medicinal Chemistry, 2018)
Thioflavone derivatives are the thio analogs of the core constituent of the natural product class of flavones. Based on the position and oxidation level of sulfur, they can be divided into three major categories: 4-thioflavones, 1-thioflavones and 1-thioflavones 1,1-dioxide. In recent years, great efforts have been made to develop an approach for the synthesis of thioflavones, especially 1- thioflavones with high functional group compatibility, high yields, low toxicity as well as proceeding under a mild condition, and a variety of synthetic protocols have been developed, the method of choice being dependent on the nature of substrates. As isosteric analogs of biologically active flavones, thioflavones also exhibit various pharmaceutical properties, such as antimicrobial, anticancer and neuroprotective activities. Replacement of the oxygen atom on flavone skeleton by a sulfur atom resulted in modified biological effects due in most part to the change of the structural properties. However, these varying effects depend on the substituents present and the test species. To provide a comprehensive vision of this class of compounds, this review primarily focuses on the structure, synthetic methods, biological properties as well as structure-activity relationships of thioflavones.
Keywords: antimicrobial